Make-Up Therapy for Patients With Facial Nerve Palsy. (August 2019) - Fujiwara, Keishi; Furuta, Yasushi; Aoki, Wakae; Nakamaru, Yuji; Morita, Shinya; Hoshino, Kimiko; Fukuda, Atsushi; Homma, Akihiro
Objectives: To investigate the effectiveness of make-up therapy for patients with facial nerve palsy. Methods: Seven female patients with facial nerve palsy who received specialist make-up therapy were enrolled. The objective of the make-up therapy was to obtain a symmetrical facial appearance. Results: Overall score for the Facial Clinimetric Evaluation (FaCE) scale was significantly improved after make-up therapy. There was a tendency for symptoms of depression to be improved among patients after make-up therapy. Conclusion: Make-up therapy to improve the symmetry of facial appearance could afford a noninvasive and low-cost treatment for patients with facial nerve palsy, especially in terms of patient quality of life and psychological condition.